Factors shaping good and poor nurse-client relationships in maternal and child care: a qualitative study in rural Tanzania - Kahabi Isangula; Eunice S. Pallangyo; Columba Mbekenga; Eunice Ndirangu-Mugo; Constance Shumba (BMC, 2022)
Abstract Background Evidence indicates that poor nurse-client relationships within maternal and child health (MCH) continues to impact trust in formal healthcare systems, service uptake, continuity with care and MCH outcomes. This necessitates contextualized innovative solutions that places both nurses and clients at the forefront as agents of change in optimizing intervention designs and implementation. This study explored nurses and clients' perspectives on the factors shaping nurse-client relationships in MCH care to generate evidence to guide subsequent steps of human centered design (HCD) that involve designing effective strategies for improving therapeutic relationships in Shinyanga, Tanzania. Methods Qualitative descriptive design was employed. About 9 Focus Group Discussions (FGDs) and 12 Key Informant Interviews (KIIs) with purposefully selected nurses and midwives, women attending MCH services and administrators were conducted using semi-structured interview guides in Swahili language. Data were transcribed and translated simultaneously, managed using Nvivo Software and analyzed thematically. Results Factors shaping nurse-client relationships were heuristically categorized into nurse, client and health system factors. Nurse contributors of poor relationship ranged from poor reception and hospitality, not expressing care and concern, poor communication and negative attitudes, poor quality of services, job dissatisfaction and unstable mental health. Client contributors of poor relationship include being 'much know', late attendance, non-adherence to procedures and instructions, negative attitudes, poor communication, inadequate education and awareness, poverty, dissatisfaction with care, faith in traditional healers and unstable mental health. Health system contributors were inadequate resources, poor management practices, inadequate policy implementation and absence of an independent department or agency for gathering and management of complaints. Suggestions for improving nurse-client relationship included awards and recognition of good nurses, improving complaints mechanisms, continued professional development, peer to peer learning and mentorship, education and sensitization to clients, improving service quality and working conditions, improving renumeration and incentives, strengthening nursing school's student screening and nursing curriculum and improving mental health for both nurses and clients. Conclusions The factors shaping poor nurse- client relationships appear to extend beyond nurses to both clients and healthcare facilities and system. Implementation of effective interventions for addressing identified factors considering feasibility and acceptance to both nurses and clients using novel strategies such as HCD could pave the way for employing good nurse-client relationships as a tool for improving performance indicators and health outcomes within MCH care.